Natural disasters and the demand for health insurance - Ha Trong Nguyen; Francis Mitrou (Global Labor Organization (GLO), 2024)
Amidst growing concerns over heightened natural disaster risks, this study pioneers an inquiry into the causal impacts of cyclones on the demand for private health insurance (PHI) in Australia. We amalgamate a nationally representative longitudinal dataset with historical cyclone records, employing an individual fixed effects model to assess the impacts of various exogenously determined cyclone exposure measures. Our findings unveil that both contemporaneous and preceding cyclones, particularly those of greater severity, substantially increase the likelihood of individuals procuring PHI. The largest estimated impact amounts to over 4 percentage points, representing approximately 8% of the sample mean and aligns with documented effects of certain PHI policies aimed at enhancing coverage. Furthermore, our findings withstand a series of sensitivity assessments, including a placebo test demonstrating that future cyclones do not impact current PHI enrolment. Moreover, the cyclone impacts are more pronounced for females, younger individuals, homeowners, affluent individuals, or those with prior residential insurance coverage, as well as residents of rural and coastal areas or historically cyclone-exposed regions. Additionally, our study furnishes suggestive evidence hinting at a potential rise in risk aversion among affected individuals as a channel through which cyclones increase PHI uptake.
Keywords: D81; G22; I13; Q54; 330; Natural Disasters; Risk Preferences; Health Insurance; Australia